Patients with symptomatic permanent atrial fibrillation show quantitative signs of pain sensitisation. (14th October 2021) - Jackson, A; Frobert, O; Boye Larsen, D; Arendt-Nielsen, L; Bjorkenheim, A
Abstract: Background/Introduction: Most patients with atrial fibrillation (AF) report symptoms, while around one-third are asymptomatic. We hypothesized that sensory processing, in particular pain, differs in patients with symptomatic and asymptomatic AF. Purpose: To assess differences in pain sensitisation in patients with symptomatic and asymptomatic AF. Methods: Thirty individuals with permanent AF (15 symptomatic, 15 asymptomatic) completed the AF6 and SF-36 questionnaires and underwent quantitative pain sensitisation testing using pressure algometry at the sternum (referred pain area) and the tibialis anterior muscle (generalized pain area). The primary objective was to assess differences in pressure pain thresholds (PPT), temporal summation of pain (TSP), and conditioned pain modulation (CPM) in the two groups. The secondary objective was to determine association of demographic and clinical parameters to quantitative measures of pain sensitisation. Results: The symptomatic group had lower PPTs at both tibialis (p=0.004) and sternum (p=0.01), as well as impaired CPM (p=0.025) and facilitated TSP (p=0.008) at the tibialis but not sternum, compared to the asymptomatic group. The AF6 sum score was negatively correlated to PPT on both tibialis (r=−0.50, p=0.005) and sternum (r=−0.42, p=0.02) and positively correlated to TSP of both tibialis (r=0.57, p=0.001) and sternum (r=0.45, p=0.01), but not to CPM. The physical component summary score was positively correlated to the PPT on both tibialis (r=0.52, p=0.003) and sternum (r=0.40, p=0.03) and negatively to TSP on the tibialis (r=−0.53, p=0.003) but not sternum. Conclusions: Patients with symptomatic AF exhibit lower pain tolerance than patients with asymptomatic AF, as well as impaired pain inhibitory control and facilitated summation of pain, indicating that pain sensitisation may be of importance in symptomatic AF. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Department of Cardiology, Örebro University, Sweden